Complete brood failure in an altricial bird is almost always associated with the sudden and permanent disappearance of a parent. (12th June 2018) - Santema, Peter; Kempenaers, Bart
Abstract: A central goal in evolutionary ecology is to identify factors that explain variation in reproductive success, i.e. in the number of offspring produced. In altricial birds, a substantial part of this variation is determined by the number of nestlings that die before fledging, but surprisingly little is known about the proximate causes of offspring mortality during the nestling period. We used a uniquely comprehensive dataset of parental nestbox visits from seven breeding seasons to investigate the association between parental behaviour and nestling mortality in a population of blue tits ( Cyanistes caeruleus ). In almost all nests that suffered complete brood mortality one of the parents had suddenly disappeared during the nestling stage. In contrast, parental disappearance in nests with partial brood mortality was rare and equally common as in nests with no brood loss. With few exceptions, parents that disappeared during the nestling stage were never observed again and never returned to breed. In contrast, parents that remained after their partner disappeared were equally likely to be observed again or return to breed as parents of nests where both parents stayed. Visit rates at nests where a parent would disappear did not differ from those at nests where both parents stayed. Taken together, our results show that ‐ in contrast to partial brood failure ‐ complete brood failure is almost always associated with the sudden and permanent disappearance of one of the parents, probably due to predation. Partial and complete brood mortality should be treated as distinct processes that have different underlying causes. Abstract : Uniquely detailed nest visit data show that partial brood loss and complete brood mortality have different underlying causes in blue tits. Contrary to what is often assumed, complete brood mortality is almost always associated with the sudden and permanent disappearance of one of the parents, probably due to predation. (Photo by Julius Kramer).